Comparison of Different Types of Concrete Slabs under Dynamic Loading - Lubna Mohammed Abd (International Journal of Scientific Research in Civil Engineering, 2025)
Structural loads are generally the forces affecting any structural element, and these loads are taken into account when designing according to the type of structure. In general the loads are divided into static and dynamic. The research studies the effect of dynamic load on the concrete slabs.   In the practical part, six different types of concrete slabs were taken as (normal concrete NC, self-compacting concrete SCC, high strength concrete HSC, fly ash concrete FAC, modified reactive powder concrete MRPC and reactive powder concrete RPC) with dimensions (450*450*50) mm had been mixed, cured and tested with their control specimens (three cubes, three cylinders and two prisms). These slabs were tested under the drop ball impact test. The device of this test was consisting of iron arm and iron frame with iron ball of 1 kg and the drop height is fixed of 1 m. From the recorded results, the Reactive Powder Concrete (RPC) had the maximum average compressive strength of 199.8 MPa, maximum number of strokes was 155 and the lowest crack width about 1.3 mm.
Keywords: Drop Ball; Fly Ash; High Strength; Steel Fibers; Slabs